Name Selection in the Novel of “Hibernation” Written by Goli Taraghi - Soheila Farhangi; Ashrafossadat Rasht-Behesht (Matn/Pizhūhī-i Adabī, 2019)
The novel of “hibernation” written by Goli Taraghi is one of the contemporary Persian stories in which the writer has used symbol, myth and old pattern. While reading stories such as this one, reader involves in reasons of choosing characters’ names, or using adjective, pronouns and … instead of names or why some characters are anonymous. The aim of this research is to study and analyze characters’ names in the novel “hibernation”. In this research, first of all, names are divided based on their types such as proper noun, common noun, adjective and compound names, then they were studied from other points of view such as meaning, characterization, perspective and …., finally frequency of each name is mentioned to see which are used more. The research method is correlative–analytical, and show that in the novel “hibernation” men and women names are chosen based on different method. Also name morphology indicates that choosing names is not random, and there are various reasons for each one.